Photochemical trajectory modelling studies of the 1987 Antarctic spring vortex - Jones, R. L.; Austin, J.; Mckenna, D. S. (1988)
Simulations of Antarctic ozone photochemistry performed using a photochemical model integrated along air parcel trajectories are described. This type of model has a major advantage at high latitudes of being able to simulate correctly the complex interaction between photolysis and temperature fields, which, because of the polar night cannot be represented accurately in a zonally averaged framework. Isentropic air parcel trajectories were computed using Meteorological Office global model analyses and forecast fields from positions along the ER-2 flight paths during the Airborne Antarctic Ozone Experiment in Austral Spring 1987. A photochemical model is integrated along these trajectories using the aircraft observations to initialize constituent concentrations. The model includes additional reactions of the ClO dimer and also bromine reactions, which are thought to play a significant role in Antarctica. The model also includes heterogeneous reactions which are invoked when the air parcel passes through a polar stratospheric cloud (PSC). The existence of a PSC is determined throughout the course of the model integration from the parcel temperature and the saturated vapour pressure of water over an assumed H2O/HNO3 mixture. The air parcel temperature is used to determine the saturated vapor pressure of HNO3 over the same mixture. Mixing ratios which exceed saturation result in condensation of the excess in the model and hence lead to a reduction of the amount of gas phase NO2 available for chemical reaction.